Sequência didática para aprender gramática: uma possibilidade metodológica para os anos iniciais do ensino fundamental - Paula, Mariana Corrêa de (2018)
This dissertation is the result of a research carried out on grammar teaching in the initial years of elementary school, with reference to the didactic organization called Didactic Sequence for Learning Grammar (SDG) proposed by Anna Camps as well as by her research group (GREAL / Autonomous University of Barcelona / Spain). The teaching of grammar, in this perspective, implies a research activity on the language, which includes, in this process, observation, analysis and manipulation of this object of knowledge. At the beginning, in this text, we present the trajectory of teaching Portuguese Language and the problematic that surrounds its teaching for language speakers, after having discussed the place of grammar in Portuguese Language classes. Subsequently, concepts were revised, including language, grammar, Portuguese language teaching and linguistic reflection. In the sequence there is an identification of the contributions from academic researches of grammar teaching, the exposition and the production process, the description and the analysis of a methodological proposal to learn grammar based on Catalan group propositions. The methodological conduct was based on principles of action research in the collaborative mode. To do so, the research was developed by the teacher-researcher, in her class of action in the 4 th year of a private school in the city of Passo Fundo / RS, in a collaborative partnership with the researcher of the Studies Group and Research on Literacy (GEPALFA), Rosângela Hanel Dias. It is concluded that this research provided, throughout the development of the didactic sequence (SDG), a reflection on the use of language by the researcher and the students.